Genome-wide association analyses identify two susceptibility loci for pachychoroid disease central serous chorioretinopathy - Hosoda, Yoshikatsu; Miyake, Masahiro; Schellevis, Rosa L.; Boon, Camiel J. F.; Hoyng, Carel B.; Miki, Akiko; Meguro, Akira; Sakurada, Yoichi; Yoneyama, Seigo; Takasago, Yukari; Hata, Masayuki; Muraoka, Yuki; et al. (Communications biology, 2019)
The recently emerged pachychoroid concept has changed the understanding of age-related macular degeneration (AMD), which is a major cause of blindness; recent studies attributed AMD in part to pachychoroid disease central serous chorioretinopathy (CSC), suggesting the importance of elucidating the CSC pathogenesis. Our large genome-wide association study followed by validation studies in three independent Japanese and European cohorts, consisting of 1546 CSC samples and 13,029 controls, identified two novel CSC susceptibility loci: TNFRSF10A-LOC389641 and near GATA5 (rs13278062, odds ratio = 1.35, P = 1.26 × 10 −13 ; rs6061548, odds ratio = 1.63, P = 5.36 × 10 −15 ). A T allele at TNFRSF10A-LOC389641 rs13278062, a risk allele for CSC, is known to be a risk allele for AMD. This study not only identified new susceptibility genes for CSC, but also improves the understanding of the pathogenesis of AMD. Yoshikatsu Hosoda et al. present a genome-wide association study in Japanese and European cohorts, identifying genes related to central serous chorioretinopathy pathogenesis. They report two novel susceptibility loci, one of which is a known risk allele for age-related macular degeneration.